The Mystery of Tomato Flu in India (Medicine Today, 2023)
Introduction: While the globe fights against monkeypox and the coronavirus, a new virus known as "Tomato flu" threatens. This virus's recognized target is children. In May 2022, the virus was found for the first time in Kerala, India. Due to its principal symptom, tomato-shaped blisters all over the body, the ailment was given the term "Tomato Flu." Recent reports described it as type of hand, foot and mouth disease (HFMD). It is easily diagnosed by a history and physical examination. It is an infectious condition, but there are still a lot of unanswered questions. To shed light on this topic, we decided to collect and summarize the information on this novel viral pathogen.Materials and Methods: To accomplish this, we undertook a thorough literature assessment of the Tomato Flu research that has already been done. We analyzed data from various sources such as medical journals, government reports and news articles to gain a better understanding of this emerging disease. In addition, we conducted interviews with healthcare professionals who have treated patients with Tomato Flu to gain insights into their experiences.Results: Survey of literature showed that Tomato Flu is a self-limiting disease. Children under the age of 5 and immunocompromised individuals are more susceptible to this disease. There is no diagnostic test for the disease, differential diagnosis involves typical symptoms and the absence of other known viral agents. There is no treatment, supportive care brings relief.Conclusion: Overall, this review provides a better understanding of Tomato Flu and its potential impact on public health. By shedding light on this emerging virus, we hope to contribute to ongoing efforts to prevent and treat of this infectious disease.Medicine Today 2023 Vol.35(2): 129-133